Role of complement activation in anti-neutrophil cytoplasmic antibody-associated glomerulonephritis - Kojima, Tadasu; Oda, Takashi (Frontiers in Medicine, 2022)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an autoimmune disease characterized by necrotizing inflammation of small or medium vessels, causing ANCA associated glomerulonephritis (AAGN). AAGN is defined as pauci-immune glomerulonephritis with no or little immune deposition; hence, activation of the complement system in AAV was overlooked until recently. However, many studies in mice and humans have revealed a crucial role for complement system activation in the development of AAGN. Circulating and urinary detection of various complement components associated with AP activation, which have been broadly correlated with the clinical activity of AAGN, has been reported and may be useful for predicting renal outcome at the time of diagnosis and setting up personalized treatments. Moreover, recent investigations have suggested the possible contribution of the complement classical or lectin pathway activation in the development of AAGN. Thus, as therapeutic options targeting complement components are making rapid strides, the primary complement pathway involved in AAGN disease progression remains to be elucidated: this will directly impact the development of novel therapeutic strategies with high specificity and reduced side effects. This review summarizes and discusses the most recent evidence on the crucial roles of the complement system in the development of AAGN and possible therapeutic strategies that target complement components for disease management.